A comparison of Mallampati scoring, upper lip bite test and sternomental distance in predicting difficult intubation - Varghese, Arun; Mohamed, Taznim (International Journal of Research in Medical Sciences, 2017)
Background: Difficult or failed tracheal intubation has been identified as one of the most important causes of death or permanent brain damage during anaesthesia. The present study has aimed to compare modified Mallampati score, Upper lip bite test and sternomental distance for predicting difficult intubation in adult patients. Methods: In this study 199 patients aged 18-60 years were recruited who were undergoing elective surgeries requiring endotracheal intubation. All patients were evaluated using modified Mallampati score, upper lip bite test and sternomental distance. Laryngoscopy was assessed by an attending anaesthesiologist blinded to the measurements and graded according to Cormack and Lehane’s grading system. Specificity, sensitivity, predictive positive value (PPV), predictive negative value (PNV), accuracy and agreement with larygoscopic grading were calculated for each parameter. Results: Specificities for modified Mallampati, upper lip bite test and sternomental distance were 65.6, 98.9 and 94%, respectively. All the tests had a NPV more than 90%, indicating that, these tests can be good predictors of easy intubation. Sternomental distance showed greatest agreement with laryngoscopic grading (kappa = 0.536, P<0.001) as well as maximum area under the ROC curve (0.955). Conclusions: The high specificity, NPV, PPV and accuracy of sternomental distance compared to other tests makes it the single best test in predicting difficulty intubation. However, a combination of all three tests was found to be more sensitive and had higher discriminative power compared to any single test alone.